Determination of SFRP1 and SFRP2 Genes Promoter Methylation Status in Patients with Chronic Myelogenous Leukemia - Elahe Derakhshanfar; Shaban Alizadeh; Hassan Rafiemehr; Fateme Nadali; Ali Qasemi; Masuod Karimi; Nushin Shabab (Tehran University of Medical Sciences, 2017)
Background and Aim: Chronic myeloid leukemia (CML) is a myeloprolifrative neoplasm that is characterized by an expansion of myeloid, erythroid cells and platelets in peripheral blood and myeloid hyperplasia in bone marrow. Secreted frizzled-related protein family is a negative regulator of the Wnt signaling pathway that suppresses this signaling pathway in healthy individuals. Aberrant regulation of the Wnt signaling pathway is a prevalent theme in cancer biology, and methylation in promoter of SFRP family has been shown to cause uncontrolled cell proliferation in cancer. Chronic myeloid leukemia was the first malignancy in which the important role of Wnt signaling pathway has been described.  In the present study, we examined the methylation status of SFRP1 and SFRP2 genes in patients with CML. Materials and Methods: Blood samples were obtained from 25 healthy individuals and 33 patients whit chronic meyloied leukemia (23 male, 10 female) Then Isolated DNA was treated with sodium bisulfite and analyzed by methylation-specific polymerase chain reaction (MSP) with primers specific for methylated and unmethylated promoter sequences of the SFRP1 & -2 genes. We used Mann-Whitney u-tests to investigate the correlation between SFRP-1 and SFRP-2 genes hypermethylation and clinical parameters. Results: In CML patient hypermethyleation frequency of SFRP-1 and SFRP-2 genes were 16.1℅ and 27.2% respectively. In control group SFRP-1 and SFRP-2 genes were unmethylated. Conclusion: The present study showed that, methylation of SFRP genes also occurs in CML like other solid tumors. Therefore, the methylation of these genes may play a role in the initiation of malignant disease.